2021
DOI: 10.1186/s12888-021-03446-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of boarded psychiatric patients in adult emergency departments

Abstract: Background This study quantifies the frequency of adverse events (AEs) experienced by psychiatric patients while boarded in the emergency department (ED) and describes those events over a broad range of categories. Methods A retrospective chart review (RCR) of adult psychiatric patients aged 18–55 presenting to one of four Calgary EDs (Foothills Medical Centre (FMC), the Peter Lougheed Centre (PLC), the Rockyview General Hospital (RGH), and South H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…The number of psychiatric inpatient beds was not associated with violence escalation, probably because the correlation between the number of inpatient beds and violence escalation depended on waiting time in the emergency department. Similarly, previous research has shown that the lack of inpatient beds can lead to longer waiting times for psychiatric emergency department patients [ 22 ], which can increase the likelihood of violent incidents occurring [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of psychiatric inpatient beds was not associated with violence escalation, probably because the correlation between the number of inpatient beds and violence escalation depended on waiting time in the emergency department. Similarly, previous research has shown that the lack of inpatient beds can lead to longer waiting times for psychiatric emergency department patients [ 22 ], which can increase the likelihood of violent incidents occurring [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…La hora de llegada de los pacientes fue un hallazgo interesante. Las horas más frecuentes de llegada de los pacientes fueron entre las 10:00 a.m. y las 12:00 p.m. Este resultado es diferente a los hallazgos de otros estudios que han encontrado que la mayoría de las admisiones psiquiátricas de emergencia ocurren durante la noche y la madrugada (5,9,26) . Se necesitan más estudios para determinar si este resultado es específico del contexto de este hospital o si refleja un patrón más general en la demanda de atención psiquiátrica de emergencia del Perú.…”
Section: Discussionunclassified
“…Estos resultados sugieren que la accesibilidad a la atención psiquiátrica en entornos médicos requiere mejo-ras (8) . Además, el abordaje de pacientes con trastornos mentales en los servicios de emergencia es subóptimo debido a la falta de recursos y entornos terapéuticos disponibles, lo que retrasa el inicio del tratamiento y causa impactos posteriores en los tiempos de espera en la emergencia y cuellos de botella para otros servicios de emergencia (9) . En el contexto peruano, la atención de emergencias psiquiátricas se rige por las normativas y guías establecidas por el Ministerio de Salud (MINSA).…”
Section: Introductionunclassified
“…An observation study by Bakhsh et al 5 showed that 65% of patients boarding in the ED for psychiatric complaints had a medication error requiring an intervention, with 89% of them being errors of omission. Furthermore, a retrospective study by Major et al 6 showed that patients who experienced an adverse event such as physical and chemical restraints, security personnel intervention, and verbal or physical assault had a significantly prolonged boarding time (35 h vs. 6.5 h, p < 0.005).…”
Section: Introduction and Current Statementioning
confidence: 99%
“…Furthermore, a retrospective study by Major et al 6 showed that patients who experienced an adverse event such as physical and chemical restraints, security personnel intervention, and verbal or physical assault had a significantly prolonged boarding time (35 h vs. 6.5 h, p < 0.005).…”
Section: Introduction and Current S Tatementioning
confidence: 99%